2005
DOI: 10.1128/aem.71.3.1626-1637.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic Identification of Single Bacteria by Micro-Raman Spectroscopy: Application to Clean-Room-Relevant Biological Contaminations

Abstract: Microorganisms, such as bacteria, which might be present as contamination inside an industrial food or pharmaceutical clean room process need to be identified on short time scales in order to minimize possible health hazards as well as production downtimes causing financial deficits. Here we describe the first results of single-particle micro-Raman measurements in combination with a classification method, the so-called support vector machine technique, allowing for a fast, reliable, and nondestructive online i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
194
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(202 citation statements)
references
References 58 publications
1
194
2
2
Order By: Relevance
“…Further investigations revealed that the single‐cell spectra could be used to differentiate between growth phases of a single species, but these differences did not obscure the overall interspecies discrimination 29. On the other hand, a previous study30 found that the Raman spectra of cells in stationary phase were characterized by sharp, distinct signals whereas the spectra of cells from other phases, e.g., early logarithmic phase, exhibited low signal‐to‐noise (S/N) ratios with broad bands. Moreover, most plant pathogens always lie in a stationary state in natural environments 28.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Further investigations revealed that the single‐cell spectra could be used to differentiate between growth phases of a single species, but these differences did not obscure the overall interspecies discrimination 29. On the other hand, a previous study30 found that the Raman spectra of cells in stationary phase were characterized by sharp, distinct signals whereas the spectra of cells from other phases, e.g., early logarithmic phase, exhibited low signal‐to‐noise (S/N) ratios with broad bands. Moreover, most plant pathogens always lie in a stationary state in natural environments 28.…”
Section: Resultsmentioning
confidence: 90%
“…Spectra with an extremely poor S/N ratio or unusually large background fluorescence were discarded. The remaining spectra were subjected to quality control with the recently developed signal processing approach (rDisc)30 followed by PCA. The data processing was carried out with Matlab R2010a (The MathWorks, Inc., Natick, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Among these, vibrational techniques [3,4,5] such as Infrared [3] and Raman spectroscopy [6] showed to be especially suitable for many applications due to their non-destructive and fast methodology [7,8]. Moreover, it has been shown that very reliable recognition results can be obtained without timeconsuming cultivation steps, since it is possible to extract informative spectra from single cells [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these advantages, Raman spectroscopy is a widespread tool for a variety of tasks such as food control [8], cancer detection [13,14,15] and the identification of microorganisms [9,11]. Equipped with powerful multivariate data analysis methods, accurate recognition rates can be achieved [11,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The high level of spatial resolution achievable with modern CRM technology allowed, for example, the Raman spectroscopic characterization of microorganisms on a single cell basis [104] and enabled to establish a rapid identification technique for clinically and technically relevant pathogens [105]. Other applications of CRM of single microbial cells include the characterization of the phenotypic heterogeneity in genetically homogeneous microbial cultures [106].…”
Section: Correction Of Chromatic Aberration Artifacts In Confocal Rammentioning
confidence: 99%